Erythrocyte Profile of Pangasius hypophthalmus Feed with Rhizophora Apiculata Leaf Extract and Maintained in Net Cages - Fricilia Zissalwa; Henni Syawal; Iesje Lukistyowati (Faculty of Fisheries and Marine, Universitas Riau, 2020)
Rhizophora apiculata leaf extract has benefits as an herbal supplement that can be added to feed, because it have componds like flavonoid, tannins, saponins, terpenoids, and steroids that can improve the health of jambal fish (Pangasius hypophthalmus). This research was carried out in August to October 2019. The aim of the research was to obtain the best dose of R. apiculata leaf extract added to feed to improve the health of jambal fish as seen from total erythrocytes, hemoglobin levels, hematocrit levels, and erythrocyte morphology. The method was used an experimental method with a Completely Randomized Design (CRD) one factor of four treatment levels consisting of P0: without the addition of extracts; P1: (1.5 mg/kg); P2: (1.7 mg/kg); and P3: (1.9 mg/kg) and repeated three times so that it takes 12 units of the experiment. Maintenance is carried out for 60 days in cages net with a size of 1x1.5x1 m3 out three times, at the beginning of maintenance, 30th day, and 60th day. The best dose was in the P2 treatment (1.7 mg/kg) seen in total erythrocytes 2.57x106 cells/mm3, hemoglobin level 13.13 g/dL, hematocrit value 38.43%, absolute weight growth 38.93 g, survival rate 97,33%, and showed normal erythrocyte morphology, it was supported by water quality during the reasearch such as DO 6.4-6,9 mg/L, pH 6.1-6.8, temperature 28.2 29.50C, and ammonia 0.04-0.08 mg/L. The Blood tests were carried.